2021
DOI: 10.1038/s41467-021-22979-3
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitylation of IL-1β limits its cleavage by caspase-1 and targets it for proteasomal degradation

Abstract: Interleukin-1β (IL-1β) is activated by inflammasome-associated caspase-1 in rare autoinflammatory conditions and in a variety of other inflammatory diseases. Therefore, IL-1β activity must be fine-tuned to enable anti-microbial responses whilst limiting collateral damage. Here, we show that precursor IL-1β is rapidly turned over by the proteasome and this correlates with its decoration by K11-linked, K63-linked and K48-linked ubiquitin chains. The ubiquitylation of IL-1β is not just a degradation signal trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 64 publications
6
41
1
Order By: Relevance
“…The study showed that the ubiquitination of pro-IL-1β limits the cellular level of pro-IL-1β by promoting its proteasomal degradation. Moreover, the ubiquitination inhibited IL-1β release through interfering with the caspase-1-mediated pro-IL-1β cleavage [136]. These results indicate that the ubiquitination of pro-IL-1β may play a role in limiting IL-1β level and caspase-1-mediated activation, which is contrary to previous studies.…”
Section: Il-1β Ubiquitinationcontrasting
confidence: 86%
See 1 more Smart Citation
“…The study showed that the ubiquitination of pro-IL-1β limits the cellular level of pro-IL-1β by promoting its proteasomal degradation. Moreover, the ubiquitination inhibited IL-1β release through interfering with the caspase-1-mediated pro-IL-1β cleavage [136]. These results indicate that the ubiquitination of pro-IL-1β may play a role in limiting IL-1β level and caspase-1-mediated activation, which is contrary to previous studies.…”
Section: Il-1β Ubiquitinationcontrasting
confidence: 86%
“…However, a more recent study suggested that K133 ubiquitination of pro-IL-1β can limit inflammasome activation [136]. The study showed that the ubiquitination of pro-IL-1β limits the cellular level of pro-IL-1β by promoting its proteasomal degradation.…”
Section: Il-1β Ubiquitinationmentioning
confidence: 98%
“…It is well accepted that K63-linked ubiquitination of pro-IL-1b is critical for inflammasome activation and IL-1b secretion (Duong et al, 2015;Vijayaraj et al, 2021). We therefore determined whether CypA influences the ubiquitination of pro-IL-1b.…”
Section: Cypa Initially Promotes and Then Inhibits Lps-induced Lung I...mentioning
confidence: 97%
“…Cleavage of IL-1β, IL-18, and GSDMD represent the final step of inflammasome activation [ 92 ]. IL-1β has one described phosphorylation site at Ser134, but its functional significance remains unknown as mutation of Ser134 did not affect the stability or secretion of IL-1β [ 93 ]. No direct phosphorylations have been described for IL-18, but both IL-1β and IL-18 are subject to significant regulation as they are transcribed as inactive pro-forms that require enzymatic cleavage for activation.…”
Section: Regulation Of Inflammasome Substratesmentioning
confidence: 99%
“…No direct phosphorylations have been described for IL-18, but both IL-1β and IL-18 are subject to significant regulation as they are transcribed as inactive pro-forms that require enzymatic cleavage for activation. They are also regulated by other PTMs, such as ubiquitylation [ 93 ]. GSDMD is the executioner of pyroptosis and to date has not been found to be directly phosphorylated [ 94 ].…”
Section: Regulation Of Inflammasome Substratesmentioning
confidence: 99%